Post-mortem Molecular Investigation: exploring genetic variation in CYP2D6 in deceased individuals at Salt River Mortuary - Vincent, Devin Michael (Division of Forensic Medicine and Toxicology, 2019)
Drug use is a major burden in Cape Town, South Africa, and at times may be fatal. Individuals suspected to have demised from drug intoxication are referred for medico-legal investigation, in order for cause of death to be determined. Sometimes, it remains ambiguous as to whether the drug intoxication was suicidal or accidental, even after a full post-mortem examination. Literature has shown that molecular analysis of genetic variants in genes encoding for drug metabolising enzymes may provide insight into the manner of death. At Cape Town’s Salt River Mortuary, numerous toxicological-related cases yield ambiguous results, which may potentially be resolved with molecular analyses. However, no optimised molecular assay to sequence drug metabolising enzymes currently exists in a local context. The aim of this project was to design and optimise a molecular-based assay to sequence the drug metabolising enzyme, CYP2D6. Subsequent to primer design, exons in CYP2D6 were amplified and sequenced. The optimised assay was then applied to DNA from two decedents suspected to have demised from drug intoxication. Following a toxicological drug screen, certain drugs metabolised by CYP2D6 were reported. The assay revealed genetic variants within CYP2D6; both individuals were heterozygous for 138insT, rendering one allele in each individual defective. While one decedent also exhibited variants with normal and unknown haplotypes, the other decedent was homozygous for *17 (decreased functionality), overall making the former an intermediate (altered) or extensive (normal) metaboliser and the latter, an intermediate metaboliser of specific drugs. Quantitative toxicological results were unavailable; consequently, the contribution of the metabolism phenotype on death in these cases could not be established. However, the genetic variants, combined with the presence of these drugs in each case, suggests altered drug metabolism, which should be investigated further and interpreted within each case context. These findings would also be beneficial to the decedents’ living relatives, who may also carry these variants. Overall, this study demonstrates the value of molecular analyses in forensic investigations of toxicological-related fatalities, and lays the foundation for additional future research, particularly since the molecular assay has now been successfully optimised.